1994
DOI: 10.1099/0022-1317-75-12-3541
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for two groups of banana bunchy top virus isolates

Abstract: Banana bunchy top virus (BBTV) DNA component 1 from isolates from 10 different countries was cloned and sequenced and the sequences were aligned and compared. This analysis indicated two groups: the South Pacific group (isolates from Australia, Burundi, Egypt, Fiji, India, Tonga and Western Samoa) and the Asian group (isolates from the Philippines, Taiwan and Vietnam). The mean sequence difference within each group was 1.9 to 3.0 % and between isolates from the two groups was approximately 10 %, but some part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
93
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(101 citation statements)
references
References 10 publications
7
93
1
Order By: Relevance
“…The species demarcation criteria for nanoviruses was based on amino acid identities of the CP gene and the members of distinct species should be \85% similarity (Vetten et al 18). Karan et al [8] characterized BBTV isolates into two distinct groups viz., Asian and South Pacific groups based on the sequences of DNA-R. We have cloned and sequenced both the CP (513 bp) and Rep (861 bp) genes from thirteen isolates and CP alone from three isolates collected from different geographic areas to assess genetic variability among the Indian isolates. When the CP gene sequences of 16 isolates were compared with isolates of South Pacific group, 97-100 nt/98-100% aa similarity was observed for 14 isolates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The species demarcation criteria for nanoviruses was based on amino acid identities of the CP gene and the members of distinct species should be \85% similarity (Vetten et al 18). Karan et al [8] characterized BBTV isolates into two distinct groups viz., Asian and South Pacific groups based on the sequences of DNA-R. We have cloned and sequenced both the CP (513 bp) and Rep (861 bp) genes from thirteen isolates and CP alone from three isolates collected from different geographic areas to assess genetic variability among the Indian isolates. When the CP gene sequences of 16 isolates were compared with isolates of South Pacific group, 97-100 nt/98-100% aa similarity was observed for 14 isolates.…”
Section: Resultsmentioning
confidence: 99%
“…BBTV DNA-R encodes a master replication initiation protein (Rep) and DNA-S encodes a viral coat protein (CP) for encapsulation (Karan et al [9]. BBTV isolates are categorized into two groups, namely the ''South Pacific group'' and the ''Asian group'' based on nucleotide sequence identity of DNA-R [8]. The mean sequence difference within each group was 1.9-3% and between isolates from the two groups was approximately 10% [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Karan et al [26] reported a distinct separation of BBTV isolates based on DNA-R, which was highly conserved within the PIO group of BBTV isolates (96.5 % identity) and within the Asian group isolates (98 % identity), but highly variable between the isolates in two groups with only 68 % identity.…”
Section: Discussionmentioning
confidence: 99%
“…Based on phylogenetic analysis of DNA-R, Karan et al [26] divided BBTV isolates into two groups such as a PIO group and South-East Asian (SEA) group. BBTV isolates from India were found to be belonging to the PIO group [6,37,41].…”
Section: Introductionmentioning
confidence: 99%